OUTCOME OF LAPAROSCOPIC TOTALLY EXTRAPERITONEAL HERNIOPLASTY FOR INGUINAL HERNIA - Hanif, Hammad; Memon, Sohail Ahmed (Journal of Ayub Medical College Abbottabad, 2015)
Background: Hernioplasty for Inguinal hernia is one of the commonest operations performed in general surgical wards. More recently, interest has waxed and waned regarding the minimally invasive approach to hernioplasty. This study was carried out to assess the management outcome of minimally invasive hernioplasty (Totally extra-peritoneal approach) as the treatment of choice for uncomplicated (incomplete and reducible) inguinal hernia. Methods: In this quasi experimental study patients aged between 14-83 years who were otherwise fit and willing for total extra-peritoneal laparoscopic repair were recruited prospectively over a 10 month period. Thirty-seven such patients were operated and followed up in the hernia clinics. Six cases were later excluded for lack of proper follow-up. Results: The typical patient was middle-aged male with right-sided inguinal hernia. Mean operating time was 53.3 minutes. No conversion was undertaken; however, there was one case of small bowel injury that went unrecognized on-table but necessitated subsequent laparotomy. Overall morbidity was 13.5%. Mean length of hospitalization was 2.89 days. Mean duration to normal routine life was 9.25 days. Overall, 70.9% of patients expressed satisfaction with the surgery. Conclusion: Totally extra-peritoneal mesh repair is a new and safe technique for hernioplasty with acceptable rates of morbidity and it is procedure of choice for recurrent and bilateral inguinal hernias and also used as alternate to open hernioplasty for uncomplicated (incomplete and reducible) inguinal hernia.